ANALISIS PENGARUH MODAL KERJA, LIKUIDITAS, DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR FOOD AND BEVERAGE DI BURSA EFEK INDONSIA PERIODE 2015-2019 - Binti Robingah (Economicus : Jurnal Ekonomi dan Manajemen, 2021)
The formulation of the problem in this study is how working capital, liquidity, and leverage affect the profitability of manufacturing companies listed on the Indonesia Stock Exchange. The purpose of this study is to determine the effect of working capital, liquidity and leverage on the profitability of the manufacturing industry listed on the Indonesia Stock Exchange. I. The number of samples in 11 companies listed on the Indonesia Stock Exchange. Data collection was obtained from the Indonesia Stock Exchange through IDX in 2015 – 2019. Data on Working Capital, current ratio (CR), Debt To Asset Return (DAR) and Return On Assets (ROA) were obtained from IDX which is a website from the Indonesia Stock Exchange. To determine the effect of work model, liquidity, and leverage on profitability using panel data. This study aims to examine and analyze the effect of Working Capital, CR, and DAR on profitability in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2015 – 2019. This research is useful for companies as consideration for determining policies, especially policies to maintain company profitability. For other researchers, it can be used as additional literature and a reference for researchers with the same theme. From this research, it can be seen that working capital, liquidity, and leverage are significantly related to the profitability of the manufacturing industry listed on the Indonesia Stock Exchange.